Mechanical adhesion of SiO2 thin films onto polymeric substrates. (3rd June 2019) - Ho, C.; Alexis, J.; Dalverny, O.; Balcaen, Y.; Dehoux, A.; Châtel, S.; Faure, B.
ABSTRACT: Quantification of adhesion between a 200 nm silicon dioxide layer and a 4.5 μm thick polymeric coating was performed by analysing the SiO2 buckle morphologies generated under compressive stress. Impacts of mechanical properties of SiO2 layers, as well as a surface pretreatment on adhesion, are shown. Interfacial toughness of both configurations are assessed using the Hutchinson and Suo model, which involves buckle dimensions determined in situ by an optical profilometer, and elastic modulus E f, of the SiO2 thin films, characterised by nanoindentation. The surface pretreatment led to initiation of buckling at a higher strain. The same trend is observed for a layer with a lower stiffness and residual stress.